THE EFFECT OF WATER TEMPERATURE AS QUENCHING MEDIA ON THE CHARACTERISTICS OF HV 350 WELD DEPOSITS - Sopiyan, Sopiyan; Basori, Basori; Susetyo, Ferry Budhi (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2020)
Hardness is a mechanical property that is needed when doing the hardfacing process. Increased violence can be generated by conducting a quenching process. The temperature of the quenching media is one of the important factors to produce maximum hardness. In this study a two-layer welding process will be carried out using HV 350 electrodes on low carbon steel then the specimens are heated in a furnace and quenching is carried out into water with two variations in water temperature namely 15 and 30 °C. Variations in water temperature during quenching produce varying hardness and microstructure. The highest hardness is produced at 15 °C where in micro photographs there are a few phases of smaller size compared to other specimens.